Derecho de imagen y la divulgación ilegal de contenidos sujetos a monetización en OnlyFans dentro del Régimen de Propiedad Intelectual Ecuatoriano. - Peñaherrera Ribadeneira, Doménica Anahí (2023)
The right of image or also known as the right to one's own image is considered as such, very personal of the human being since it allows him to decide on the communication of his physical image in different areas, however this right has been violated by the illegal dissemination that exists in digital platforms where the content is nourished by the physical image of the person, thus affecting the integrity, privacy and even economy of the creator while there is no legal regulation that punishes or is specifically adapted to this special situation. The research project sought to make known the consequences of the violation of the right of image as a very personal right of the human being, as well as the deviant approach that exists in the virtual world, the risks and exposures to which it is subjected by the illegality of the disclosure of content on digital platforms subject to monetization, such as OnlyFans, the existing damage and harm to the person who uses his image as a means of marketing. Likewise, the existing gaps in the current legislation on the subject were highlighted, as well as in the Intellectual Property regulations that regulate the content linked to the right of image as if it were a trademark. Through a descriptive research we sought to address the problem by means of the "what" is happening with respect to the problem focused on the violation of the right of image related to its legal part. Together with the explanatory research, we will delve not only into the existence of the problem, but also into its causes. The results were found focused on demonstrating the existence of the violation of the right of image in digital platforms that are subject to monetization, the affectation at xii both personal and material level of content creators who use their image as a source of economic income, the lack of regulations that can regulate and control the risks to which these people are involved, and to solve this gap in the norm through a legal proposal that meets the object of aid generated as a result of this problem. Keywords: image right, onlyfans, monetization, content creator, owner.